(untitled) (Baghdad Science Journal, 2009)
This in order to test the effect of food on growth and fecundity, two kinds of food have been used the algae Scendesmus quadricaudae and fresh water shrimp powder. For two generations, growth and productivity have been followed up. The fresh water shrimp has been noticed as a food better than algae, because it caused recording, for the two generation higher length rate for the weeks of experiment. The individuals length rate at the end of the forth week reached 9.35 and 9.48 mm for the first generation and second generation respectively. The average length weekly increase rate for the first and second generations individuals feeding on dried shrimp was higher through the first and second week compared to what was recorded when feeding algae. The results showed that the fecundity of the individuals feeding on dried better than those feeding on algae. These individuals got matured in about 15 – 18 days old for the first generation and about 16 – 18 days old for the second generation s. Broods number for the two generation was four; the resulting generation was as nuplii larvae. The average number of the generation nauplii was 55.53, 61.20, 16.13 and 57.73 nauplii per mother for the four broads respectively. The average number of the second generation was 56.56,58.10,61.73 and 49.96 nauplii per mother for the four broods respectively . The individual feeding on algae S. quadricaudae recorded length rate of 7.32 and 7.43 for the first and second generation at the end of the forth week . the individuals got matured in about 19-21mm days old for the first generation and about 18-20 days old for the second generation . The first brood appeared in about 25 – 27 days old for the first generation, and about 30 – 35 days old for the second generation. The brood number was two for the first generation, the first one as nauplii larvae with a rate 40.26 larvae per mother and the second as cyst with a rate 27.90 cysts per mother. For the second generation individuals, one brood has been appeared from which the resulting generation was as cysts with a rate of 45.66 cysts per mother.